One-Step High-Temperature Electrodeposition of Fe-Based Films as Efficient Water Oxidation Catalysts - Kamlesh (Langmuir : the ACS journal of surfaces and colloids, 2023)
Electrolysis of water to produce hydrogen requires an efficient catalyst preferably made of cheap and abundant metal ions for the improved water oxidation reaction. An Fe-based film has been deposited in a single step by electrochemical deposition at temperatures higher than the room temperature. Until now, the electrodeposition of iron oxide has been carried out at 298 K or at lower temperatures under a controlled atmosphere to prohibit atmospheric oxidation of Fe2+ of the iron precursor. A metal inorganic complex, ferrocene, and non-aqueous electrolyte medium propylene carbonate have been used to achieve electrodeposition of iron oxide without the need of any inert or controlled atmosphere. At 298 K, the amorphous film was formed, whereas at 313 K and at higher temperatures, the hematite film was grown, as confirmed by X-ray diffraction. The transformation of iron of the ferrocene into a higher oxidation state under the experimental conditions used was further confirmed by X-ray photoelectron spectroscopy, ultraviolet-visible, and electron paramagnetic resonance spectroscopic methods. The films deposited at 313 K showed the best performance for water oxidation with remarkable long-term electrocatalytic stability and an impressive turnover frequency of 0.028 s-1 which was 4.5 times higher than that of films deposited at 298 K (0.006 s-1). The observed overpotential to achieve a current density of 10 mA cm-2 was found to be 100 mV less for the film deposited at 313 K compared to room-temperature-derived films under similar experimental conditions. Furthermore, electrochemical impedance data revealed that films obtained at 313 K have the least charge transfer resistance (114 Ω) among all, supporting the most efficient electron transport in the film. To the best of our knowledge, this is the first-ever report where the crystalline iron-based film has been shown to be electrodeposited without any post-deposition additional treatment for alkaline oxygen evolution reaction application